Near‐glacier surveying of a subglacial discharge plume: Implications for plume parameterizations. Issue 13 (3rd July 2017) - Jackson, R. H.; Shroyer, E. L.; Nash, J. D.; Sutherland, D. A.; Carroll, D.; Fried, M. J.; Catania, G. A.; Bartholomaus, T. C.; Stearns, L. A.
Abstract: At tidewater glaciers, plume dynamics affect submarine melting, fjord circulation, and the mixing of meltwater. Models often rely on buoyant plume theory to parameterize plumes and submarine melting; however, these parameterizations are largely untested due to a dearth of near‐glacier measurements. Here we present a high‐resolution ocean survey by ship and remotely operated boat near the terminus of Kangerlussuup Sermia in west Greenland. These novel observations reveal the 3‐D structure and transport of a near‐surface plume, originating at a large undercut conduit in the glacier terminus, that is inconsistent with axisymmetric plume theory, the most common representation of plumes in ocean‐glacier models. Instead, the observations suggest a wider upwelling plume—a "truncated" line plume of ∼200 m width—with higher entrainment and plume‐driven melt compared to the typical axisymmetric representation. Our results highlight the importance of a subglacial outlet's geometry in controlling plume dynamics, with implications for parameterizing the exchange flow and submarine melt in glacial fjord models. Key Points: 3‐D structure and transport of a subglacial discharge plume from novel near‐glacier surveying Observed plume is inconsistent with axisymmetric plume theory commonly used to model submarine melt and near‐glacier circulation Observations point toward a wider plume that drives higher entrainment and more submarine melting